Technological innovation and the bank lending channel of monetary policy transmission - Iftekhar Hasan; Xiang Li; Tuomas Takalo (Halle Institute for Economic Research (IWH), 2023)
This paper studies whether and how banks' technological innovations affect the bank lending channel of monetary policy transmission. We first provide a theoretical model in which banks' technological innovation relaxes firms' earning-based bor rowing constraints and thereby enlarges the response of banks' lending to mone tary policy changes. To test the empirical implications, we construct a patent-based measurement of bank-level technological innovation, which can specify the nature of technology and tell whether it is related to the bank's lending business. We find that lending-related innovations significantly strengthen the transmission of the bank lending channel.
Keywords: E52; G21; G23; 330; bank lending channel; FinTech; innovation; monetary policy transmission